Teachers' Perceptions on Using ICT Tools in Teaching and Learning process: An Example of Northern Cyprus Secondary Schools - Aljawadi, Fatimah Salih Khalleefah (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
Information, Communication, and Technologies have become extremely common within a very short period of time, known one of the basic building blocks of modern society. Integration of ICT will assist teachers to the global requirement to replace traditional teaching methods with a technology-based teaching and learning tools and facilities. The study aimed at investigating the extent of Information and Communication Technology (ICT) consumption in teaching and learning, examining the effectiveness of ICT in teaching and learning and finally establishes the factors which restrict the use of ICT in teaching and learning by teachers in secondary schools in Northern Cyprus. In this research, data is collected via quantitative method. A descriptive survey design was implemented for this study. A convenience sampling method is carried out to collect data. A questionnaire was delivered to 182 teachers of secondary schools. The collected date were analyzed through SPSS (Statistical Package for the Social Sciences). The results of this research show that most of the respondents view a high level of importance on their attitudes towards implementing ICT. In addition, a high level of awareness is reported in teachers in secondary schools displaying higher responses in their level of the ICT usage. Furthermore, the study distinguishes different opinions between male and female teachers in regards to ICT allowing students to be more creative and imaginative. There are also significant dissimilarities of secondary school teachers on their opinion perceptions on being confident with ICT and also in response to students learning more effectively by the consumption of ICT for instructing and learning purposes. However, the result of study indicates that there is not significant differences among teachers’ perceptions according to their age, gender and teaching experience. Keywords: Information and Communication (ICT), Teachers' Perceptions, ICT effectiveness, Teaching and Learning, secondary schools, Northern Cyprus

ÖZ: Bilgi ve İletişim Teknolojileri kısa bir sürede, büyük ölçüde yaygınlaşarak modern toplumun temel taşlarından biri haline gelmiştir. BİT kullanımının eğitime entegre edilmesi, öğretmenlerin, geleneksel eğitim yöntemlerinin yerini alan ve teknoloji temelli eğitim, öğretim araçları ile olanakları sunan evrensel gereksinimlere ulaşmasına destek sağlamaktadır. Bu çalışma, Kuzey Kıbrıs'ta bulunan ortaokullarda görev yapan öğretmenlerin katılımıyla, eğitim ve öğretimde Bilgi ve İletişim Teknolojileri'nin (BİT) tüketimini, etkisini ve son olarak BİT kullanımını sınırlayan faktörleri araştırmayı amaçlamaktadır. Bu araştırmada kullanılan veriler nicel yöntemlerle toplanmıştır. Çalışmada, betimleyici bir anket tasarısı uygulanmıştır. Verileri toplamak amacıyla uygun örnekleme yöntemi kullanılmıştır. Ortaokullarda eğitim veren 182 öğretmene anket ulaştırılmıştır. Toplanan veriler ise SPSS (Statistical Package for theSocialSciences) yazılımı aracılığıyla analiz edilmiştir. Çalışmanın bulguları, katılımcıların çoğunun BİT kullanımına yönelik tutumlarına yüksek seviyede önem verdiğini göstermektedir. Buna ek olarak, daha yüksek seviyede BİT kullanımına dair yanıt veren ortaokul öğretmenlerinde daha yüksek düzeyde farkındalık gözlemlenmiştir. Ayrıca bu çalışma, BİT kullanımının öğrencilerin yaratıcılığı ve hayal gücü üzerindeki etkisiyle ilgili olarak erkek ve kadın öğretmenler arasındaki farklı görüşleri de ortaya çıkarmıştır. Elde edilen bulgulara göre, öğretmenlerin BİT kullanımında kendilerine duydukları güvenle ilgili algılarında farklılıklar gözlemlenmiştir. Ders ile öğrenim amaçlarına yönelik BİT kullanımının, öğrencilerin öğrenmesinde daha etkili olduğu konusundaki görüşlerde de farklılıklar gözlemlenmiştir. Ancak, öğretmenlerin görüşlerinde yaş, cinsiyet ve eğitmenlik deneyimine göre belirgin bir fark gözlemlenmemiştir. Anahtar Kelimeler: Bilgi ve İletişim Teknolojileri (BİT), Öğretmen Algısı, BİT etkililiği, Eğitim ve Öğretim, ortaokul, Kuzey Kıbrıs.
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2018. Supervisor: Prof. Dr. Mustafa İlkan.
Keywords: Computer Education and Instructional Technologies Department; Information and Communication Technologies in Education--Teachers' Perceptions--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Education - Computer network resources--E-Learning; Mobile communication systems in education; Schools--Teaching, Aids and Devices; Educational Technology--Educational Media--E-Learning; Teaching Aids--Teaching Materials--Teaching Equipments--Instructional materials; Teaching - Computer network resources; Information and Communication (ICT); Teachers' Perceptions; ICT effectiveness; Teaching and Learning; secondary schools; Northern Cyprus